Treatment of Obstructed Defecation - Ellis, C. Neal; Essani, Rahila (Clinics in Colon and Rectal Surgery, 2012)
Obstructed defecation is a common problem that adversely affects the quality of life for many patients. Known causes of obstructed defecation include pelvic dyssynergy, rectocele, rectal intussusception, enterocele, pelvic organ prolapse, and overt rectal prolapse. Management of this condition requires an understanding of urinary, defecatory, and sexual function to achieve an optimal outcome. The goal of surgical treatment is to restore the various pelvic organs to their appropriate anatomic positions. However, there is a poor correlation between anatomic and functional results. As the pelvis contains many structures, a pelvic support or function defect frequently affects other pelvic organs. Optimal outcomes can only be achieved by selecting appropriate treatment modalities that address all of the components of a patient's problem.
Keywords: rectocele; pelvic dyssynergy; biofeedback; enterocele; rectal prolapse